Birth timing after the long feeding migration in northern elephant seals - Condit, Richard; Beltran, Roxanne S.; Robinson, Patrick W.; Crocker, Daniel E.; Costa, Daniel P. (Dryad, 2021)
A prominent phase of the annual cyle in migratory animals is the
transition between migration and reproduction. The transition is a small
part of the annual cycle, but details of its timing deserve attention.
From a distant location, animals must initiate a long migration so that
they arrive at the breeding ground on a precise schedule. Here we take
advantage of a sample of female northern elephant seals that were tracked
by satellite during their migration prior to parturition. In these
animals, we could estimate the time interval between arrival and birth,
allowing tests of the following hypotheses: 1) More experienced mothers
could time arrival more precisely and thus reduce the pre-parturition
interval. 2) Mothers in poor body condition were forced to forage longer
and thus shorten the interval. 3) Late-arriving mothers had a shorter
interval because they foraged longer. We also calculated the distance
traveled in the last two weeks of the migration to examine females'
ability to control arrival time, hypothesizing that animals further from
the colony traveled back at a higher speed.
Seals were identified by numbered plastic tags attached to their flippers,
allowing individuals to be tracked throughout their 22-year lifespans.
ARGOS satellite transmitters, GPS, and Time-Depth Recorders were deployed
on individuals to document movements while at sea. The instruments were
attached prior to foraging migrations and removed immediately thereafter.
While the animals were sedated, detailed morphometric measurements were
collected, allowing percent body fat to be calculated; percent fat was
assumed to reflect female condition. When satellite records showed animals
near the colony, daily searches were carried out in order to observe them
on the breeding beaches and find their newborn pups. The table below
documents 106 cases in which there was no gap between the last day a
female was seen without a pup and the first with a pup. In all, the time
of birth was known with a precision of 24 hours, while the time of arrival
was known within a few minutes from satellite and depth tracks, so the
delay between arrival and birth could be estimated with a precision of one
day.
The table includes observations from 106 female migrations ending at the
Año Nuevo colony in California. It is tab-delimited ascii. The columns
are: animalID: Unique individual identifier season: Year of birth (arrival
dates were in Dec of previous year in several cases) age: Age of female in
years (85 of the records have age) adate: Arrival date, Year-month-day
format aday: Arrival day (days since 1 December of the year before season)
firstwith: First day with a pup (days since 1 December) dist15: Distance
from colony (km) 15 days prior to birth (99 of the records have distances)
dist10: Distance from colony (km) 10 days prior to birth dist5: Distance
from colony (km) 5 days prior to birth distmax: Maximum distance from
colony (km) during entire migration prior to birth
Keywords: Animal Ecology